2023
DOI: 10.1039/d2nr06801j
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-responsive and biocompatible nanocarriers based on clay nanotubes for controlled anti-cancer drug release

Abstract: Administration of temperature-responsive drug carriers that release anticancer drugs at high temperatures can benefit the hyperthermia therapies because of the synergistic effect of anticancer drug molecules and high temperature on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…On the other hand, thermal stimulation has a vasodilating effect and alters the permeability of tumor cell membranes, thus facilitating the delivery of antitumor drugs and local drug concentration, and enhancing the antitumor effect. Heat-sensitive materials are usually temperature-controlled by a temperature-sensitive material in a nanosystem, which triggers a change in the nanosystem upon warming, triggering drug release [92,93]. Typically, thermosensitive nanosystems remain stable at 37°C and can trigger rapid drug delivery after reaching 40-42°C, minimizing drug leakage due to blood circulation and metabolism at the tumor site [31].…”
Section: Temperature-responsive Nanocarriersmentioning
confidence: 99%
“…On the other hand, thermal stimulation has a vasodilating effect and alters the permeability of tumor cell membranes, thus facilitating the delivery of antitumor drugs and local drug concentration, and enhancing the antitumor effect. Heat-sensitive materials are usually temperature-controlled by a temperature-sensitive material in a nanosystem, which triggers a change in the nanosystem upon warming, triggering drug release [92,93]. Typically, thermosensitive nanosystems remain stable at 37°C and can trigger rapid drug delivery after reaching 40-42°C, minimizing drug leakage due to blood circulation and metabolism at the tumor site [31].…”
Section: Temperature-responsive Nanocarriersmentioning
confidence: 99%
“…Drug delivery systems are recognized as efficient adjuvant therapy for bone tumors to avoid the strong side effects caused by conventional chemotherapy and also to probe the tumor and surrounding area to obtain images for monitoring potential events associated. , Clinical studies have shown that nanomaterials loaded with antitumor drugs can circumvent the side effects caused by systemic administration to the greatest extent compared to free drugs. These nanocarriers can improve drug permeability by sensing environmental stimuli (such as pH, temperature, magnetism, and ultrasound), enhancing the permeability retention effect, and lengthening circulation time to realize passive targeting. …”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, Hemmatpour et al [17] have synthesized a drug loaded carrier based on the surface modi ed HNT. For this purpose, polydopamine was coated on the surface of HNT, then atom transfer radical polymerization (ATRP) agent was adhered on the surface, and nally poly(N-isopropylacrylamide) (PNIPAM) chains were grown on the surface via a grafting from approach.…”
Section: Introductionmentioning
confidence: 99%